Geotextile biofiltration of primary treated municipal wastewater under simulated arctic summer conditions. Issue 6 (December 2016) - Bridson-Pateman, Evan; Jamieson, Rob; Lake, Craig
Abstract: Wastewater stabilization ponds (WSPs) are common for wastewater treatment in remote Canadian Arctic communities. In this paper, two geotextiles of different mass/unit areas are examined as a potential biofiltration upgrade to existing WSPs in arctic summer conditions. The intended role of the geotextile is to provide additional treatment of municipal wastewater seeping from these WSPs. Column filtration experiments were performed using municipal wastewater in a controlled laboratory environment at either 10 °C or 2 °C. The columns contained one of two different nonwoven geotextiles over 10 cm of gravel, simulating a WSP berm in contact with exfiltrating wastewater. Weekly wastewater samples were taken upstream and downstream of the geotextile/gravel filter and were analyzed for a suite of water quality parameters; the hydraulic conductivity of the columns was also measured weekly. Results showed that it is possible to accumulate biomass on geotextile material over a 3 month period at these temperatures, which corresponded with 1–2 log reductions in hydraulic conductivity. Significant removal of total suspended solids, 5-day biochemical oxygen demand, total nitrogen, and total phosphorus was observed; however, removal efficiencies for most parameters were reduced at the lower temperature. This study demonstrates that geotextiles could be used to enhance the performance of WSP systems operating in arctic climates.